2022
DOI: 10.1007/s11747-022-00892-5
|View full text |Cite
|
Sign up to set email alerts
|

Artificial empathy in marketing interactions: Bridging the human-AI gap in affective and social customer experience

Abstract: Artificial intelligence (AI) continues to transform firm-customer interactions. However, current AI marketing agents are often perceived as cold and uncaring and can be poor substitutes for human-based interactions. Addressing this issue, this article argues that artificial empathy needs to become an important design consideration in the next generation of AI marketing applications. Drawing from research in diverse disciplines, we develop a systematic framework for integrating artificial empathy into AI-enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 127 publications
0
36
0
1
Order By: Relevance
“…Augmented reality is defined as a “medium in which digital information is overlaid on the physical world that is in both spatial and temporal registration with the physical world and that is interactive in time” (Craig, 2013; p. 20). From a marketing perspective, two of the main benefits of chatbots enabled by artificial intelligence are powerful personalization and the option to automate services offered to customers (Ameen et al, 2022; Chandra et al, 2022; Liu‐Thompkins et al, 2022; Mariani et al, 2022). Chatbots have been defined as “an e‐service agent that represents a technological evolution of the traditional service agent involved in direct firm–customer exchanges” (Murtarelli et al, 2020; p. 2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented reality is defined as a “medium in which digital information is overlaid on the physical world that is in both spatial and temporal registration with the physical world and that is interactive in time” (Craig, 2013; p. 20). From a marketing perspective, two of the main benefits of chatbots enabled by artificial intelligence are powerful personalization and the option to automate services offered to customers (Ameen et al, 2022; Chandra et al, 2022; Liu‐Thompkins et al, 2022; Mariani et al, 2022). Chatbots have been defined as “an e‐service agent that represents a technological evolution of the traditional service agent involved in direct firm–customer exchanges” (Murtarelli et al, 2020; p. 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…20). From a marketing perspective, two of the main benefits of chatbots enabled by artificial intelligence are powerful personalization and the option to automate services offered to customers (Ameen et al, 2022;Chandra et al, 2022;Liu-Thompkins et al, 2022;Mariani et al, 2022).…”
Section: Augmented Reality and Chatbots In The Customer Journeymentioning
confidence: 99%
“…The performed in-depth context analysis of the existing literature has shown that large attention is paid to the issue of the social consequence of the transition to the AI economy. Liu-Thompkins et al (2022) substantiate the existence of artificial empathy in marketing interactions and the need to bridge the human-AI gap in affective and social customer experience. Lew and Walther (2022) assess the international practice of communication between humans or chatbots and AI and determine social scripts and expectancy violations.…”
Section: Theorymentioning
confidence: 75%
“…The current study revealed that Russian consumers are already deeply embedded in the CX individualization . The trend towards CX individualization is visible in the recent events for practitioners (e .g ., [Client Service Forum, 2022]), in online retailers' practice (e .g ., Ozon or L'Etoile), and academic research [Hoyer et al ., 2020;Liu-Thompkins et al ., 2022] . One can assume that this trend represents an answer to an earlier call to go away from using discounts as the only way to create value and fight for the customer facing decreasing consumer income [Nielsen, 2018] .…”
Section: Discussionmentioning
confidence: 99%
“…11] . Interaction humanization implies that a firm empathetically react to customer inquiries, which can be realized through the combination of human and digital solutions that allow understanding the emotions of potential and real customers [Kulikova, Suvorova, 2022;Liu-Thompkins et al ., 2022] . One of the most popular technology-enabled ways to humanize customer-firm interaction is through cognitive and empathetic chatbots [Kozoriz, 2019;Behera, Bala, Ray, 2021;Agarwal, Maiya, Aggarwal, 2021] .…”
Section: Individualization Strategiesmentioning
confidence: 99%